Detection of citrus viroids by multiplex reverse transcription polymerase chain reaction (RT-PCR) - Roslin, Nor Athirah (2017)
Citrus from family Rutaceae is a perennial plant that found in subtropical and tropical regions including Malaysia. One of the problems in citrus is the infection of viroids such as Citrus exocortis viroid (CEVd), Citrus bent leaf viroid (CBLVd), Citrus viroid III (CVd-III) and Citrus viroid IV (CVd-IV). Symptoms of viroid infections are bark shelling, leaf necrosis, bending of leaf margin and dwarfing. CBLVd has been reported in Malaysia which is associated with yield loss. However, symptoms are not enough to prove that particular viroid is the causes of that infection. Multiplex RT-PCR has been reported to detect multiple viruses and viroids in plants. Multiplex RT-PCR was used in this study to detect the citrus viroids simultaneously in citrus samples. Citrus samples showing viroid infection like symptoms was taken; 16 samples from Kajang and 10 samples from UPM, Selangor, 6 samples from Jaya Gading, 2 samples from Sri Damai, and 4 samples from Semambu Kuantan, Pahang and 25 samples from Bertam Jaya, Melaka. The RNA extract from all 63 leaf samples was used for the amplification of the viroids using 4 different primers sets using multiplex RT-PCR. The analysis showed 10 out of 63 samples (1 sample from UPM, Selangor and 9 samples from Bertam Jaya, Melaka) produced amplicons at 200-300 bp. The other 53 samples (16 samples from Kajang, 9 samples from UPM, Selangor, 6 samples from Jaya Gading, 2 samples Sri Damai, and 4 samples from Semambu Kuantan, Pahang) showed negative results with no amplicon produced. These positive results were obtained from C. hystrix from UPM, Selangor and C. microcarpa from Bertam Jaya, Melaka. RT-PCR analysis of 9 positive results produced amplicon approximately 200-300 bp by specific primer set, CV-I-cp and CV-I-hm. Sequencing analysis for four samples (1 sample from UPM, Selangor and 3 samples from Melaka) showed high sequence similarity with Citrus bent leaf viroid Ia genomic RNA, isolate: Jp, complete genome (GenBank: AB006734.1) ranged from 91-100%. No other citrus viroids were detected in this experiment using the multiplex RT-PCR.